病人自主決定與醫療行善: Patients’ Determination vs. Physicians’ Beneficence - CUI, Hong (International Journal of Chinese & Comparative Philosophy of Medicine, 1999)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 通過對“喉梗阻”患兒案例的分析和感受，本文試圖分別從醫生、患者和哲學研究者的角度進行較客觀的思考。從醫生的角皮看：“自主決定”和醫療行善存在矛盾，削弱了醫生的“自主”決定，醫生的角色是單純的醫療技術掌握者還是用此技術全心全意為病人服務的行善者？從患者的角度看：患者是否都有“自主決定”的能力？若醫生只是單純的醫療技術的掌握者，與患者無情感的溝通，患者在醫院是否有心理上的安全感？從思考者的角度看：在前面論述的基礎上，提出了“善”是相對的，“自主”是適度的，任何絕對的病人自主和醫生自主都行不通。總之，醫療行善，不能拘泥於某一形式。 It is important to respect for patients’ rights. The patient should be informed of medical interference and the physician must obtain the patient’s consent to perform serious treatment. This is a sense of patients’ self-determination in contemporary medical practice. This paper argues that, granted its importance, patients’ self-determination should not be given unique emphasis independent of physicians’ medical beneficence. The paper considers this issue from both Chinese physicians’ and patients’ perspectives. First, from the physician’s perspective, the role of the physician as a professional ought not to be overlooked. Should the physician play a role no more than that of an ordinary salesman by displaying everything for the customer to choose? Traditionally Chinese medicine has always insisted that the physician should do more than. Having studied both human and technical values, the physician should play an active function to help the patient make the right decision. He should not passively follow whatever the patient chooses on the excuse of respecting for the patient’s self-determination. Instead, being physician, he is naturally determined to do medical beneficence toward the patient. Of course, there may be fundamental value conflicts between the patient and the physician. For instance, they may believe in different religions. This difference may sometimes lead the patient to want or refuse something that the physician takes to be against the patient’s interest. In such cases the physician and patient may best respect each other’s fundamental values. However, most medical cases are unlike this. They don’t involve any fundamental value conflict. The physician should do his best to persuade the patient to make the right decision, rather than passively to accept whatever the patients chooses. Moreover, Chinese patients’ perspective also supports physicians’ beneficence. The patient would say this. Look, the physician has been trained specially in their work. Technically they should know better regarding what the patient should do. Being sick is a weak time in the patient’s life. The patient does not want to confront it lonely. On the one hand, the patient wants the family to take care of her and take the burden of making the decision in her best interest. On the other hand, the patient wants the physician to help the family in this difficult process of decision making. It is not appropriate for the physician to play a role of salesman and leaves everything in my hands. This is against the nature of physicians as the beneficent healers. In short, both Chinese physicians’ and patients’ perspectives support the combination of patients’ determination and physicians’ beneficence. It is inappropriate simply to stress the importance of patients’ rights or self-determination without giving significant weight to the role of medical beneficence that physicians should play in medical practice. DOWNLOAD HISTORY | This article has been downloaded 17 times in Digital Commons before migrating into this platform.